2011
DOI: 10.3892/ol.2011.370
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of vitamin B6 reduces colonic damage and protein expression of HSP70 and HO-1, the anti-tumor targets, in rats exposed to 1,2-dimethylhydrazine

Abstract: Abstract. Mounting evidence indicates that vitamin B6 is a protective factor for colon cancer. Elevations in colonic damage, cell proliferation and heat shock proteins (HSPs, molecular chaperones) have been suggested to be associated with colon carcinogenesis. This study was performed to examine the effect of dietary levels of vitamin B6 (1, 7 or 35 mg pyridoxine HCl/kg diet) for 22 weeks on colon damage, epithelial cell proliferation and expression of HSPs in rats exposed to 1,2-dimethylhydrazine (DMH). Suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Consistent with these previous results, the current study observed that dietary vitamin B6 intake, from a supplemental vitamin B6 diet to a low vitamin B6 diet, caused a marked reduction in colon tumorigenesis in mice exposed to azoxymethane (5). Our animal studies suggest that the anti-colon tumor effect of dietary vitamin B6 is partially ascribed to lowering colon cell proliferation, oxidative stress, inflammation and epithelium cell damage (5)(6)(7)(8). Furthermore, we observed that vitamin B6 inhibited lipopolysaccharide (LPS)-induced expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in mouse macrophage RAW264.7 cells via suppression of nuclear factor-κB (NF-κB) activation (9).…”
Section: Introductionsupporting
confidence: 80%
“…Consistent with these previous results, the current study observed that dietary vitamin B6 intake, from a supplemental vitamin B6 diet to a low vitamin B6 diet, caused a marked reduction in colon tumorigenesis in mice exposed to azoxymethane (5). Our animal studies suggest that the anti-colon tumor effect of dietary vitamin B6 is partially ascribed to lowering colon cell proliferation, oxidative stress, inflammation and epithelium cell damage (5)(6)(7)(8). Furthermore, we observed that vitamin B6 inhibited lipopolysaccharide (LPS)-induced expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in mouse macrophage RAW264.7 cells via suppression of nuclear factor-κB (NF-κB) activation (9).…”
Section: Introductionsupporting
confidence: 80%
“…Consistently, increasing epidemiological evidence indicates vitamin B 6 acts as a protective factor against colon cancer (3)(4)(5)(6). We also reported that vitamin B 6 decreases oxidative stress, inflammation, cell proliferation, epithelial cell damage, and angiogenesis, which may lead to lower tumorigenesis (1,2,(7)(8)(9)(10). Moreover, we recently found that high concentrations of pyridoxal (PL) increase the expression of insulin-like growth factor-binding protein 1 (IGFBP1), a putative tumor suppressor, in human hepatoma (HepG2) cells via the upregulation of the ERK/c-Jun pathway (11).…”
Section: Introductionsupporting
confidence: 50%
“…A couple of years later, however, the antitumor activity of L-canavanine, a precursor of L-canaline, was shown to be independent of its intracellular conversion into L-canaline, casting doubts on the true relevance of Rosenthal's findings. 71 Later on, the interest on the potential antineoplastic effects provided by vitamin B6 antagonists dropped and most of the preclinical studies on vitamin B6 aimed at testing its potential cytoprotective effects, [72][73][74][75] and hence whether it might be employed to limit the adverse effects of radio-and chemotherapy. 76,77 In 2012, our group has demonstrated that PN synergizes with a large panel of chemotherapeutics (including the DNA-damaging agent cisplatin) as well as several chemotherapy-unrelated stress conditions (for example, hyperthermia, hypoxia, nutrient deprivation, irradiation, inhibition of the respiratory chain and endoplasmic reticulum stress) in the killing of a large panel of cancer cells in vitro.…”
Section: Preclinical Observationsmentioning
confidence: 99%